Glorifikasi Kebebasan Dari Penjara Figur Publik Pelaku Kekerasan Seksual di Infotainment Indonesia - Wiwid Adiyanto; Putri Ayu Sabrina (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2023)
Freedom from prison for perpetrators of child sexual abuse, who is also a public figure, was warmly welcomed by fans and relatives. The excitement was inseparable from the infotainment coverage that was broadcast through the mass media. On the other hand, sexual violence has physical and psychological consequences that affect the lives of the victims. The presence of infotainment programs also creates debate, especially in the realm of journalism related to ethics. This study attempts to describe the inequality of coverage of Saipul Jamil's freedom from prison as a former inmate who perpetrates sexual violence on the infotainment program Intens Investigasi. This study places the Critical Discourse Analysis developed by Norman Fairclough as an analytical knife. The results of this study indicate that the glorification carried out by infotainment related to freedom from prison, public figures who are perpetrators of sexual violence have a tendency to normalize sexual violence, especially in public figures. Infotainment texts lead to dispensation for public figures who commit sexual violence. Gender literacy, sexual violence, and the media are absolutely necessary, both for media people and the wider community. In addition, a grassroots movement is needed to stop the glorification that leads to the normalization of sexual violence.